2019
DOI: 10.2147/jhc.s168953
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lenvatinib for the treatment of unresectable hepatocellular carcinoma: evidence to date</p>

Abstract: During the last 10 years, the multikinase inhibitor sorafenib has emerged as the only systemic treatment for unresectable hepatocellular carcinoma (HCC). More recently, data from the Phase III REFLECT trial showed that another multikinase inhibitor, namely, lenvatinib, was non-inferior to sorafenib in terms of overall survival (OS). In contrast, with respect to OS, previous randomized Phase III trials have been negative, and several agents tested have failed to prove non-inferiority (or superiority) when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…After bioinformatics prediction, we identified miR-3619-5p may be a target miRNA of DGCR5, and their direct interaction was confirmed by dual-luciferase assay. Previous studies have revealed that miR-3619-5p plays a tumor suppressive role in various cancers [19,36,37]. Then we conducted a series of loss/gain-of-function assays to explore the expression pattern and biological role of miR-3619-5p in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…After bioinformatics prediction, we identified miR-3619-5p may be a target miRNA of DGCR5, and their direct interaction was confirmed by dual-luciferase assay. Previous studies have revealed that miR-3619-5p plays a tumor suppressive role in various cancers [19,36,37]. Then we conducted a series of loss/gain-of-function assays to explore the expression pattern and biological role of miR-3619-5p in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, the HCC incidence rates depend on the factors including race/ethnicity, gender, age, and geo‐/demographic regions and also by several risk factors such as cirrhosis, hepatitis B (HBV) infection, hepatitis C (HCV) infection, excessive alcohol consumption, nonalcoholic fatty liver disease (NAFLD), obesity, diabetes, glucose overload, metabolic syndrome, and environmental toxic intake (Fig. ) . The development of HCC is complex, involving sustained inflammatory damage leading to hepatocyte necrosis, regeneration, and fibrotic deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib, a targeted drug, has been shown to be effective in prolonging HCC patient survival; however, the use of sorafenib is limited due to the high cost. 38 Therefore, it is very meaningful to screen out a drug that can improve the sensitivity of sorafenib. Studies had shown that SK enhanced the sensitivity of non-small cell lung cancer to erlotinib and gefitinib.…”
Section: Discussionmentioning
confidence: 99%